2006
DOI: 10.1525/jer.2006.1.4.9
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Paying Research Participants: It's Time to Move beyond the Ethical Debate

Abstract: CURRENT REGULATORY GUIDELINES REQUIRE the ethical review committee to consider one question when evaluating payment: Is the payment to the participant undue or coercive? Although this is a seemingly simple question, determining appropriate payment involves a series of complex issues. There is limited empirical knowledge to assist with this determination and little consensus on which elements of a study should be considered in making these decisions. For example, should the culture of the study population or th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 52 publications
2
43
0
Order By: Relevance
“…The majority of participants were motivated to join the study for altruistic or financial reasons. Our findings confirm that previous research on willingness to participate in HIV-prevention trials may apply to participants in a microbicide trial [7,10,11] and add to the body of literature showing that, although compensation plays a part in motivation to enroll and return for follow-up, a combination of factors that also include altruism and personal convenience is at play [28,29]. …”
Section: Discussionsupporting
confidence: 88%
“…The majority of participants were motivated to join the study for altruistic or financial reasons. Our findings confirm that previous research on willingness to participate in HIV-prevention trials may apply to participants in a microbicide trial [7,10,11] and add to the body of literature showing that, although compensation plays a part in motivation to enroll and return for follow-up, a combination of factors that also include altruism and personal convenience is at play [28,29]. …”
Section: Discussionsupporting
confidence: 88%
“…The positive and negative impact of payment for study participation in actual studies have been shown for survey (Coogan & Rosenberg, 2004; Doody et al, 2003; Gilbart & Kreiger, 1998; Little & Davis, 1984; Parkes et al, 2000; Perneger, Etter, & Rougemont, 1993), HIV risk reduction (Deren et al, 1994), and substance abuse studies (Festinger et al, 2005; Fry & Dwyer, 2001). The ethical debate regarding paying participants is also not new and laws and guidelines establish the concept that payment should not be coercive or undue, as has been extensively discussed (Grady, 2005; Permuth-Wey & Borenstein, 2009; Ripley, 2006). Payment practices vary for similar national studies (Grady, 2005) but little empirical data exists to determine how investigators choose payment and how IRB members review payment.…”
mentioning
confidence: 99%
“…As other community research has found, incentives can serve as leverage with those living in poverty in the DTES, making it difficult for individuals to refuse to participate in research even where ethical concerns exist (Damon et al, 2017). This type of inducement runs counter to conventional research ethics guidelines (Dunn & Gordon, 2005;Medical Research Council of Canada, 1987;Ripley, 2006), which assert that financial gain should not be a primary motivation for participation in research. These findings speak to the need to address economic deprivation among this population, alongside ensuring research results in material improvements for marginalized communities.…”
Section: "Where Does All This Information Go?" the Practice Of (Un)inmentioning
confidence: 99%